MicroRaman spectroscopy detects the presence of microplastics in human urine and kidney tissue - Massardo, Sara; Verzola, Daniela; Alberti, Stefano; Caboni, Claudia; Santostefano, Matteo; Eugenio Verrina, Enrico; Angeletti, Andrea; Lugani, Francesca; Ghiggeri, Gian Marco; Bruschi, Maurizio; Candiano, Giovanni; Rumeo, Noemi; et al. (Environment international, 2024)
[Display omitted] •Recent evidence reports microplastics’ presence in human tissues and fluids.•MicroRaman spectroscopy is employed to detect microplastics in biological samples.•66 microparticles fragments were found in 10 kidney tissues and 10 urine samples and 26 out 66 were characterized.•SpeComp open-access software was developed to ease microRaman spectra comparison.•The most often detected pieces and pigments are polyethylene, polystyrene, hematite. There is a growing concern within the medical community about the potential burden of microplastics on human organs and tissues. In this study, we investigated by microRaman spectroscopy the presence of microplastics in human kidneys and urine. Moreover, an open-access software was developed and validated for the project, which enabled the comparison between the investigated spectra and a self-created spectral database, thus enhancing the ability to characterize polymers and pigments in biological matrices. Healthy portions of ten kidneys obtained from nephrectomies, as well as ten urine samples from healthy donors were analyzed: 26 particles in both kidney and urine samples were identified, with sizes ranging from 3 to 13 μm in urine and from 1 to 29 μm in kidneys. The most frequently determined polymers are polyethylene and polystyrene, while the most common pigments are hematite and Cu-phthalocyanine. This preclinical study proves the presence of microplastics in renal tissues and confirms their presence in urine, providing the first evidence of kidney microplastics deposition in humans.